STOMACH CANCER: ACTUAL QUESTIONS AND WAYS OF THEIR IMPLEMENTATION - Arman Khozhayev; Akaisha Sarina; Talgat Baitileuov; Maxim Stadnikov; Berik Djumabekov; Yuliya Ilakhunova; Yerbossyn Sembayev (Foundations and Trends in Modern Learning, 2024)
This scientific and analytical work presents modern global and local-regional data on incidence, mortality, lethality and five-year survival rate of such a common oncological pathology as stomach cancer. The issues related to risk factors, etiopathogenesis, peculiarities of spread and clinical manifestations, as well as measures for the prevention of this formidable disease are covered in detail. The epidemiological characteristics of this nosological form of malignant neoplasms in our republic in the context of the regions of the country are given